PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PERIKANAN KABUPATEN KAMPAR - Gazali R; Zulfadil Zulfadil; Samsir Samsir (Jurnal Ekonomi, 2018)
This study aims to analyze the influence of leadership and organizational culture on job satisfaction and employee performance and the effect of job satisfaction on employee performance. The population in this study is all the employees in Dinas Perikanan Kabupaten Kampar as many 55 people. The sample size that will be used is 55 people. Data used in this research are primary data and secondary data. Data collection methods used by the authors in this study is by using Questionnaire. Data analysis method used is descriptive and quantitative. Descriptive is used to provide an overview of the data. Quantitative, ie analysis by collecting, categorizing and tabulating data, using the WarpPLS approach.The research found that the value of leadership variables are in good category. Furthermore, leadership influence on job satisfaction and employee performance. That is, good leadership is a leader who can make employees feel satisfied with their work and ultimately can improve performance. The values of organizational culture variables are in fairly good category. Furthermore, organizational culture affect the job satisfaction and performance of employees. This means that with a good organizational culture, able to provide satisfaction to employee satisfaction and ultimately the performance of employees will increase. The variable value of satisfaction is in the category quite well. Furthermore, job satisfaction affects employee performance. This means that the higher the satisfaction obtained by employees to make employees work with the maximum, so that employees will work optimally to improve employee performance.